Characteristics and Activity of Anti Qourum Sensing Bacillus spp. Isolated from Penaeus vannamei Shrimp Ponds - Iman Rusmana; Yuni Puji Hastuti; Rizal Khoirun Alfisah; Alina Akhdiya (HAYATI Journal of Biosciences, 2021)
Certain strains of V. parahaemolyticus carry a gene that encodes a toxin that causes Acute hepatopancreatic necrosis disease (AHPND) in P. vannamei. AHPND attacks shrimp post larvae within 20-30 days after stocking causing up to 100% mortality. The expression of these virulent genes is controlled by the quorum sensing system. This system is inhibited by an anti-quorum sensing (AQS) mechanism. Several Bacillus strains have AQS mechanism by producing AHL-Lactonase enzyme. Therefore, this study aimed to obtain Bacillus spp. having AQS activity for controlling AHPND. The study was conducted from isolation and selection of Bacillus isolates, as well as determination of AQS activity. From 22 samples consisting of shrimp intestines, water and pond sediment samples, a total of 151 isolates of Bacillus spp. were isolated. The screening test for AQS activity obtained 11 isolates that showed AQS activity on Cromobacterium violaceum. Determination of violacein pigment in liquid cultures of C. violaceum showed the index value of the pigment formation was between 0.025-0.166 and 0.026-0.567 at 24-hour and between 48-hour incubations, respectively. The quantitative analysis of violacein production showed that there were six isolates of Bacillus could inhibit the pigment production more than 75%. The isolates were identified as Bacillus cereus (four isolates), Bacillus thuringiensis (one isolate), and Bacillus velezensis (one isolate), respectively. The molecular analysis had confirmed that the isolates have aiiA genes encoding AHL-lactonase enzyme. These Bacillus isolates have potential application for controlling AHNPD disease.